Combinational Sensitization of Leishmania with Uroporphyrin and Aluminum Phthalocyanine Synergistically Enhances their Photodynamic Inactivation in vitro and in vivo() - Dutta, Sujoy (2012)
Leishmania were previously shown to undergo photolysis when their transgenic mutants were induced endogenously to accumulate cytoplasmic uroporphyrin or when loaded exogenously with aluminum phthalocyanine chloride. A combinational use of both is reported here, which renders Leishmania far more susceptible to photolysis. Fluorescence microscopy of cells loaded with the two photosensitizers localized them to different subcellular sites. Pre-exposure of Leishmania to both synergistically sensitized them for photolysis as extracellular promastigotes and as intracellular amastigotes in infected macrophages in vitro when illuminated at specific wavelengths to excite the respective photosensitizers for production of reactive oxygen species. Both Leishmania stages lost their viability completely when doubly photosensitized optimally and illuminated at low intensity, the host cells being left unscathed. Inoculation of mice with photo-inactivated Leishmania produced no lesions, which invariably developed in the control groups during a period of observations for eight weeks. Pre-treatment of Leishmania with both photosensitizers rendered these cells susceptible to clearance from the ear dermis by white light illumination. The results suggest that double photosensitization for synergistic activity enhances the efficacy and safety of photodynamic therapy in general and for Leishmania in particular.